KONSEP TASAMUH DI INDONESIA PERSPEKTIF M. QURAISH SHIHAB DALAM TAFSIR AL-MISBAH (Studi Analisis Penafsiran Surah al-An’am Ayat 108) - Nur Azizah; Muh. Fatoni Hasyim (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2023)
Indonesia is an archipelagic country that has a diversity of cultures, races, ethnicities, beliefs, religions and languages. In addition, they also adhere to various religions and beliefs such as Islam, Hinduism, Buddhism, Catholicism, Christianity, Protestantism, Confucianism and hundreds of local religions or beliefs that have become part of the local culture. Islam is one of the religions in this country, and the Koran is the main reference as a way of life. Of course, in this religion there are many teachings that are oriented to the benefit of the people, such as religious moderation. Among the principles of religious moderation, one that will be discussed in this article is the concept of tasamuh in Indonesia from the perspective of M. Quraish Shihab. The method used in this article is qualitative. The results of his research show that the contextualization of the tasamuh principle or what is commonly referred to as tolerance is found in surah al-An'am verse 108. In this case, Quraish Shihab explains that this verse talks about the prohibition for Muslims not to insult the worship of other religions. . If we draw on the concept of tasamuh in Indonesia, of course this in accordance with existing conditions, because considering this country is a country that has a diversity of ethnicities, races, cultures and religions. So, the concept of tasamuh is certainly appropriate to be applied in order to maintain the integrity of this nation.